Recent Advances in Micro-Electro-Mechanical Devices for Controlled Drug Release Applications - Villarruel Mendoza, Luis Abelardo; Scilletta, Natalia Antonela; Bellino, Martin Gonzalo; Desimone, Martin Federico; Catalano, Paolo Nicolas (Frontiers in Bioengineering and Biotechnology, 2020)
In recent years, controlled release of drugs has posed numerous challenges with the aim of optimizing parameters such as the release of the suitable quantity of drugs in the right site at the right time with the least invasiveness and the greatest possible automation. Some of the factors that challenge conventional drug release include long-term treatments, narrow therapeutic windows, complex dosing schedules, combined therapies, individual dosing regimens, and labile active substance administration. In this sense, the emergence of micro-devices that combine mechanical and electrical components, so called micro-electro-mechanical systems (MEMS) can offer solutions to these drawbacks. These devices can be fabricated using biocompatible materials, with great uniformity and reproducibility, similar to integrated circuits. They can be aseptically manufactured and hermetically sealed, while having mobile components that enable physical or analytical functions together with electrical components. In this review we present recent advances in the generation of MEMS drug delivery devices, in which various micro and nanometric structures such as contacts, connections, channels, reservoirs, pumps, valves, needles and/or membranes can be included in their design and manufacture. Implantable single and multiple reservoir-based and transdermal-based MEMS devices are discussed in terms of fundamental mechanisms, fabrication, performance and drug release applications.